A Comprehensive Systematic Review of The Relationship Between Intra-Articular Corticosteroid Use and Cartilage Damage - Satya Agung Nugroho; Nazalla Gwen Vaganesha; Agus Saribudaya (The International Journal of Medical Science and Health Research, 2025)
Introduction: Intra-articular corticosteroid (IACS) injections are a cornerstone treatment for symptomatic osteoarthritis and inflammatory arthropathies. However, significant controversy persists regarding their long-term effects on articular cartilage, with studies reporting outcomes ranging from chondroprotective to chondrodestructive. This systematic review synthesizes the current evidence on the relationship between IACS use and structural cartilage damage. Methods: A comprehensive systematic review was conducted following predefined screening criteria. Eligible studies examined IACS effects on cartilage using validated structural assessment methods (e.g., MRI, histology, radiography) with follow-up ≥3 months. Data from 80 included studies—including RCTs, cohort studies, animal studies, and systematic reviews—were extracted regarding study design, corticosteroid protocol, patient characteristics, assessment methods, and cartilage outcomes. A qualitative synthesis was performed, focusing on reconciling conflicting findings through analysis of dose-response relationships, temporal patterns, and joint-specific effects. Results: The evidence demonstrates substantial heterogeneity. High-quality RCTs, such as McAlindon et al. (2017), found that repeated triamcinolone injections every 3 months for 2 years caused significantly greater cartilage volume loss compared to saline. Similarly, studies by Saif-ur-Rehman et al. (2022) and Haddad et al. (2000) reported increased disease progression and histological cartilage damage. Conversely, multiple studies, including Raynauld et al. (2003) and Şahin et al. (2023), found no significant cartilage damage with single or infrequent injections. A clear dose-response relationship was identified, with low doses (≤3 mg/dose) potentially beneficial and high cumulative doses (>18-24 mg) associated with damage. The hip and temporomandibular joints appeared more vulnerable than the knee. Baseline disease severity, obesity, and injection frequency were significant effect modifiers. Discussion: The apparent conflict in the literature is largely explained by differences in treatment protocols (dose, frequency, duration), joint-specific vulnerability, and patient characteristics. The balance between the potent anti-inflammatory benefits of IACS and their potential catabolic effects on cartilage matrix is delicate and context-dependent. The findings underscore that IACS are not uniformly "good" or "bad" for cartilage; their impact is modulated by clinical context. Conclusion: IACS injections present a dualistic effect on articular cartilage. Single or infrequent injections in the knee, particularly at low doses, appear to carry minimal structural risk and can be chondroprotective in inflammatory settings. However, repeated, high-dose injections, especially in vulnerable joints like the hip and TMJ, are associated with accelerated cartilage damage. Clinical practice should adhere to the principle of using the lowest effective dose with adequate intervals between injections, tailored to the specific joint and patient profile.